2022
DOI: 10.1007/s41324-022-00441-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temporal shifting of PM2.5, lockdown effect, and influences of seasonal meteorological factors over the fastest-growing megacity, Dhaka

Abstract: Dhaka is subjected to high pollution levels throughout the year, holding some relatively high amounts of pollution readings, making its air unhealthy to breathe. The study examined hourly, shifting, seasonal fluctuations in particulate matter (PM 2.5 ), the effects of seasonal meteorological variables, and the lockdown effect over the megacity of Dhaka from 2019 to 2021 using data from AirNow. The results indicate the daily average PM 2.5 concentration between 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, this study found that wind speed (m s −1 ) has a positive correlation (r 2 = 0.34) while air pressure (hPa) has a negative (r 2 = −0.24) correlation. Faisal et al [38] found that the Pearson correlation coefficient (r) between the PM 2.5 and meteorological variables was negative with rainfall (mm/h) (r 2 = −0.62) and humidity (kg m −2 ) r 2 = (−0.82) but positive with wind speed (m s −1 ) (r 2 = 0.09) and air temperature (k) (r 2 = −0.73) in Dhaka, Bangladesh. In addition, a Pearson correlation revealed a significant association among the pollutants, while a significant correlation was observed between PM 2.5 and surface temperature (k), which is similar to our paper's results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study found that wind speed (m s −1 ) has a positive correlation (r 2 = 0.34) while air pressure (hPa) has a negative (r 2 = −0.24) correlation. Faisal et al [38] found that the Pearson correlation coefficient (r) between the PM 2.5 and meteorological variables was negative with rainfall (mm/h) (r 2 = −0.62) and humidity (kg m −2 ) r 2 = (−0.82) but positive with wind speed (m s −1 ) (r 2 = 0.09) and air temperature (k) (r 2 = −0.73) in Dhaka, Bangladesh. In addition, a Pearson correlation revealed a significant association among the pollutants, while a significant correlation was observed between PM 2.5 and surface temperature (k), which is similar to our paper's results.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic variables have an important role in assessing PM 2.5 in rural and urban areas. The authors of [38] conducted research on the relationship between PM 2.5 and seasonal meteorological factors in Dhaka, Bangladesh, where they found that rainfall and temperature had a negative association with PM 2.5 . Rainfall was also negative in Dhaka [11].…”
Section: Introductionmentioning
confidence: 99%
“…PM 2•5 concentrations reaches their peaks in the morning and night time where it drops at evening time. The transportation sector, particularly trucks and buses, is one of the main sources of PM 2•5 emissions in Dhaka City [15]. The fact that trucks and long-distance buses are allowed to operate inside the city from 10 p.m. to 8 a.m. may be a major factor in the morning's greater PM 2•5 concentrations than in the afternoon and evening.…”
Section: Methodsmentioning
confidence: 99%
“…Bangladesh is densely populated, with cities housing more than one-third of the population, and its air quality is among the worst in the world [ 9 , 10 ]. According to a global report on air pollution and health burden, Bangladesh documented a total of 173,500 deaths due to air pollution in 2019, which is over 50,000 more than the previous year, and it has been ranked as ninth among the top ten countries with the highest level of outdoor Ambient Particulate Matter (PM 2.5), which is very small at 2.5 micrometers in diameter or less, produced by all types of combustion common in urban and rural areas [ 11 – 13 ]. The most harmful particulate matter (PM 2.5), may cause significant health effects by entering deep into the respiratory tract and caused by 74,000 fatalities in Bangladesh [ 14 ].…”
Section: Introductionmentioning
confidence: 99%